The Middle-Class Muslims’ Responses Toward the Salafi Da’wah: A Study on Hijrah celebrities - Setiana Dewi, Oki; Khoirul Fata, Ahmad; Fauzi, Mahfudh (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
This study unravels how Indonesian celebrities who submitted to Salafi Islam (popularly called hijra celebrities) responded to some notable Salafi teachings. Like in many Muslim countries, such as Türkiye, Pakistan, and Egypt, Salafism is increasingly attracting followers from the middle class who then express their Salafism in public visibility, or called “active piety”. The data for this article was collected through in-depth interviews with Salafi preachers (dais) and celebrities who actively participated in the Islamic meetings held or taught by these preachers. This study uses a cultural studies approach, in which Hall's theory of encoding-decoding is used to analyse the active role of hijrah celebrities in receiving messages conveyed by Salafi preachers. This study reveals that the Salafi preachers used the educational approach in their propagation (da’wah) through religious education forums using clear guideline books. Meanwhile, the celebrities’ responses toward this Salafi propagation varied, i.e., dominant hegemony, negotiation, and opposition, with negotiation being the most frequent. In general, the celebrities accepted the Islamic teachings from their Salafi teachers, except for several issues that they considered less relevant to their lives. This study also found the fact that the hijrah celebrities, as recipients of information, did not passively receive information, but they classified, selected, and utilised the information received from the Salafi preachers and adapted it to their needs.